Coexistence of electrical conductivity and ferromagnetism in a hybrid material formed from reduced graphene oxide and manganese oxide1. Issue 11 (21st March 2015) - Murashima, Yusuke; Ohtani, Ryo; Matsui, Takeshi; Takehira, Hiroshi; Yokota, Ryotaro; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
<x xml:space="preserve">Abstract</x> The coexistence of electrical conductivity and ferromagnetism has been achieved in a reduced graphene oxide and manganese oxide hybrid (rGO–Mn).